2007
DOI: 10.1111/j.1744-7348.2007.00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in root development of Arabidopsis promoted by organic matter from oxisols

Abstract: The presence of ramified and abundant lateral roots is fundamental to plant growth on highly weathered soils. In this work, the effects of humic acid (HA), fulvic acid and hexanic-methanolic (HM) extract, after alkaline extraction from topsoil of seven different oxisols, on the development of roots of Arabidopsis thaliana was evaluated. Furthermore, we used another emergent plant model, that is, micro-tom (MT) tomatoes with size similar to that of Arabidopsis to test the effects of HA. It was observed that bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 47 publications
(60 reference statements)
7
46
0
6
Order By: Relevance
“…ure 2). One similar curve was showed for lateral root density of Arabidopsis treated with HA isolated from Oxisols (Dobbss et al, 2007). The authors also found that inhibition concentration varies from 250 to 400 mg L -1 .…”
Section: Resultssupporting
confidence: 55%
“…ure 2). One similar curve was showed for lateral root density of Arabidopsis treated with HA isolated from Oxisols (Dobbss et al, 2007). The authors also found that inhibition concentration varies from 250 to 400 mg L -1 .…”
Section: Resultssupporting
confidence: 55%
“…The hormone-like effect, especially similar to that of auxins, as discussed by Canellas et al (2002), Nardi et al (2005), Zandonadi et al (2007) and Dobbss et al (2007), is based on the increase in formation and length of lateral roots in relation to the growth of the main root in plants treated with humic acids. For the Acrisol and Latosol, particularly in subsurface layers, the fertility is limited to the point that humic acids did not provide an effect different from the control.…”
Section: Discussionmentioning
confidence: 96%
“…Five days after germination, the seedlings were thinned to four plants per plate, and Hoogland solution modified to a final concentration of 1 mmol L -1 N was applied (Dobbss et al, 2007). Four mL of solution containing 0, 20, 40 and 80 mg L -1 of humic acids were added to each plate and 4 mL of deionized water only to the control treatment.…”
Section: Bioactivity Of Humic Acidsmentioning
confidence: 99%
See 2 more Smart Citations